A Sociolinguistics Analysis of Code-Switching Used in English Language Classroom - Umi Mujiarni; Vannia Liebnis; Dilla Sintia; Maria Arina Luardini; Natalina Asi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examines the phenomenon of code-switching that occurs in the English learning process in the informal tutoring class ProBimbel. The purpose of this study was to identify the types of code-switching used by students, the context in which code-switching occurs, and its sociolinguistic functions in teaching and learning interactions. This study used a descriptive qualitative approach, with eight prospective ProBimbel students (casis) as subjects who had an Indonesian language background and English language skills at elementary to intermediate levels. The data were collected through direct observation and audio-visual recordings of classroom activities, and were later analyzed using a systematic coding framework to identify the forms of code-switching and interpret their meanings. The results showed that intra-sentential switching was the most dominant type of code-switching (50%), followed by inter-sentential switching (25%) and tag switching (25%). The most frequent code-switching functions included clarification, expressions of misunderstanding, transitions, and opening discussions. These findings suggest that code-switching functions as an adaptive communication strategy and contextually supports the language learning process. In conclusion, code-switching is not a linguistic error but rather a reflection of developing communicative competence.